Recognition of a Fungal Effector Potentiates Pathogen‐Associated Molecular Pattern‐Triggered Immunity in Cotton - Lifan Sun; Xiangguo Li; Jiajie Zhong; Yu Wang; Baiyang Li; Ziqin Ye; Jie Zhang (Advanced Science)
Abstract Plants are equipped with multi‐layered immune systems that recognize pathogen‐derived elicitors to activate immunity. Verticillium dahliae is a soil‐borne fungus that infects a broad range of plants and causes devastating wilt disease. The mechanisms underlying immune recognition between plants and V. dahliae remain elusive. Here, a V. dahliae secretory protein, elicitor of plant defense gene (VdEPD1), acts as an elicitor that triggers defense responses in both Nicotiana benthamiana and cotton plants is identified. Targeted gene deletion of VdEPD1 enhances V. dahliae virulence in plants. Expression of VdEPD1 triggers the accumulation of reactive oxygen species (ROS) and the activation of cell death in cotton plants. Gossypium barbadense EPD1‐interacting receptor‐like cytoplasmic kinase (GbEIR5A) and GbEIR5D interact with VdEPD1. Silencing of GbEIR5A/D significantly impairs VdEPD1‐triggered cell death in cotton plants, indicating the contribution of GbEIR5A/D to VdEPD1‐activated effector‐triggered immunity (ETI). VdEPD1 stimulates the expression of GbEIR5A and GbEIR5D in cotton plants. Interestingly, cotton plants with silenced GbEIR5A/D genes exhibit compromised pathogen‐associated molecular patterns (PAMPs)‐triggered ROS accumulation, whereas overexpression of GbEIR5A or GbEIR5D enhances PAMP‐induced ROS. These findings indicate that recognition of VdEPD1 potentiates GbEIRs to enhance cotton PAMP‐triggered immunity (PTI), uncovering a cooperative interplay of PTI and ETI in cotton.